Conformational modulation of Ant-Pro oligomers using chirality alteration of proline residues - Kale, Sangram S.; Kotmale, Amol S.; Dutta, Achintya Kumar; Pal, Sourav; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2012)
Structural modulation of Ant-Pro (anthranilic acid-proline) oligomers has been carried out by chirality alteration of the proline residues. The results suggest that the chirality altered oligomers show well-defined helical conformation featuring nine-membered hydrogen bonding interactions - without compromising conformational rigidity.

Carboxamide versus sulfonamide in peptide backbone folding: a case study with a hetero foldamer - Ramesh, Veera V. E.; Kale, Sangram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic Letters, 2013)
Strikingly dissimilar hydrogen-bonding patterns have been observed for two sets of closely similar hetero foldamers containing carboxamide and sulfonamides at regular intervals. Although both foldamers maintain conformational ordering, the hydrogen-bonding pattern and backbone helical handedness differ diametrically.

Conformational modulation of peptides using beta-amino benzenesulfonic acid ((S)Ant) - Priya, Gowri; Kotmale, Amol S.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication describes the utility of a conformationally restricted aromatic beta-amino acid (2-aminobenzenesulfonic acid, (S)Ant) inducing various folding interactions in short peptides. Sandwiching (S)Ant between diverse amino acid residues was shown to form robust folded architectures featuring a variety of H-bonded networks, suggesting its utility in inducing peptide folding.

Coumarin-appended stable fluorescent self-complementary quadruple-hydrogen-bonded molecular duplexes - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Shinde, Dinesh R.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2017)
In this paper we report a coumarin-conjugated self-assembling system adorned with valuable features such as high duplex stability and a built-in fluorophore, which would augment its application potential. This system forms a highly :stalik molecular duplex in a nonpolar solvent (K-dim > 1.9 X 10(7) M-1 in CDCl3). Due to the fluorescent property of coumarin, these new structural motifs may find potential application in material chemistry and supramolecular chemistry.

Conformational studies of Ant-Pro motif-incorporated cyclic peptides: gramicidin S and avellanin - Kotmale, Amol S.; Sangtani, Ekta; Gonnade, Rajesh G.; Sarkar, Dhiman; Burade, Sachin; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2018)
This paper reports conformational changes observed in cyclic bioactive peptides such as gramicidin S and avellanin upon incorporation of a pseudo-beta (C9) Ant-(D)Pro turn motif in their structural frameworks. Solution-state studies suggested that a synthetic gramicidin S analog exhibits a beta-sheet conformation with C9 and C17 intramolecular hydrogen bonding patterns, while its truncated analog disturbs the beta-sheet conformation. Structural details were obtained using a combination of CD studies, X-ray crystal structure studies and nOe-based MD simulation studies.